Teaching the Turkish language to foreigners at higher education level in Northern Cyprus: An evaluation based on self-perceived dominant intelligence types, twenty-first-century skills and learning technologies - Karakaş Kurt, Esra; Güneyli, Ahmet (Frontiers in Psychology, 2023)
There are many foreign students in higher education in Northern Cyprus. Both the academic and life skills of these students depend on attaching the necessary importance to their Turkish language teaching. In this context, the objective of this study is to analyses university students' use of learning technologies, 21st-century skills and perceived intelligence types in the foreign language-learning process. In line with the quantitative research design, this study utilized a descriptive approach. Purposeful and convenience sampling methods were used to create the study sample. Accordingly, the university with the highest number of international students in Northern Cyprus, where the Turkish language is the medium of instruction and one of the authors of this study has been working, was selected. The study sample consisted of 431 university students who took Turkish as a foreign language in the 2021-22 academic year at the selected university. The results of the study revealed a weak yet statistically significant correlation between 21st-century skills and usage of foreign language-learning technologies. Additionally, students' 21st-century skill scores differed significantly, whereas their foreign language-learning technology scale scores did not match their self-perceived intelligence types